Killa Vive Verde consulting report - Rodrigo Antonio, Porta Oñate; Lennart, Benjamin Peters; Rabl, Wolfgang Knut; Wang, Donghui (Pontificia Universidad Católica del Perú, 2023)
This paper focuses on the analysis of Killa Vive Verde, a SME working with the Shawan Rama and the Shipibo Konibo communities to create products. The company has been facing production issues and needed advice how they can increase the production output of the indigenous artisans. After consulting with experts in the field, as well as surveying over 80 people familiar with Peruvian culture and buying norms, the current market trend and consumer thoughts could be identified. After many insightful meetings with the company, coupled with literature review and the qualitative & quantitative research, 4 potential solutions were identified. Two targeted of the motivation of the artisans, laying focus on the motivation of the communities. One focused on creating a partnership with another community to increase the artisans working in the production process. The final recommendation explored the option of increasing access to innovative tools which speed up production and stabilise communication.
Keywords: Consultores de empresas--Planificación estratégica; Pequeñas y medianas empresas--Perú; Artesanos peruanos; Comunidades nativas--Perú; https://purl.org/pe-repo/ocde/ford#5.02.04